KAJIAN HUKUM KELUARGA IRAN TERKAIT POLIGAMI DALAM KONTEKS MASYARAKAT TERTINGGAL - siti nurul hikmah siti nurani (Institut Agama Islam Darul Ulum Kandangan, 2025)
This study investigates the legal, cultural, and social complexities surrounding the practice of polygamy in Iran, focusing on its impact on women in marginalized communities. The topic was selected due to the persistent inequality faced by women, despite formal legal provisions requiring court approval and the consent of the first wife. The central hypothesis asserts that polygamy persists because of the interplay between lenient legal enforcement, entrenched patriarchy, and limited socioeconomic alternatives for women. Utilizing a qualitative socio-legal method with a case study approach, the research integrates Islamic legal theory, gender justice, and patriarchal structure analysis. The findings reveal a significant gap between legal norms and on-the-ground practices, where polygamy is often facilitated through unofficial channels, exacerbated by the legitimization of temporary marriage (mut’ah). Women involved in such marriages frequently experience economic marginalization, legal vulnerability, and psychological harm. The study concludes that legal reform alone is insufficient; achieving substantive gender justice requires cultural transformation, institutional support, and inclusive legal enforcement. The results underscore the urgency for gender-sensitive legal reform and empowerment frameworks tailored to Iran’s sociocultural context. Keywords: family law, gender justice, Iran, patriarchy, polygamy.